Expectations of orthodontic treatment in adults: the conduct in orthodontist/patient relationship - Ricardo Alves de Souza; André Frutuoso de Oliveira; Suélem Maria Santana Pinheiro; Jefferson Paixão Cardoso; Maria Beatriz Borges de Araújo Magnani (Dental Press Editora, 2013)
INTRODUCTION: The high demand for orthodontic treatment, evidenced over the last few decades, has been justified mainly by the greater importance given to facial esthetics, influencing individual's self esteem. However, the professional frequently does not meet all the patient's expectations, for not establishing good communication and not knowing about the critical points during orthodontic treatment. OBJECTIVE: The aim of this study was to elucidate patients' desires and doubts regarding orthodontic treatment, by means of a survey applied to 60 adult patients. RESULTS: The analysis of results revealed that most individuals (38.3 %) noticed treatment success after its conclusion. Occlusion deviation was pointed out by 66.7 % as the main reason for seeking treatment, and esthetics ranked as second (with 48.3 %). Treatment time was considered within the prediction by 46.7% of the interviewees and the results were judged as very good by 43.3 %. The social relations of most participants were not affected by treatment (73.3 %). Also, 58.3 % of the interviewees reported pain as the main complaint and 53.3 % found it difficult to use dental floss. Most participants saw the orthodontist as a professional who was concerned about their health (76.7 %), and believed that he/she was more able to treat them (96.6 %) when compared with the general practitioner. CONCLUSION: The orthodontist/ patient relationship enables an understanding of the expectations regarding orthodontic treatment, resulting in greater motivation and cooperation, leading to a successful outcome.